Embroidered Lines and Cut Threads: Women's Domestic Needlework in the Italian Diaspora. - Inguanti, Joseph J. (2008)
Keywords: dept.art; faculty_collection; sabbatical_report

Realm and Representation: Art and Cartography in Late Medieval France. - Serchuk, Camille (2008)
Keywords: dept.art; faculty_collection; sabbatical_report

Hysterical Sustenance: A Painted Investigation into Nature and Artiface, Food and Still Life. - Brownell, Mia (2005)
Results from sabbatical resulted in grants, peer review and extensive exhibitions. Several paintings were done examining the traditions of food as a subject in still life using genetically modified food.
Keywords: dept.art; faculty_collection; sabbatical_report

Rome as a Work of Art and 17th Century Dutch Art. - Levine, David A. (2003)
Keywords: dept.art; faculty_collection; sabbatical_report

Ozias Blue and Me. - Carr, T. Wiley (Fall;Art., 2001)
Keywords: dept.art; faculty_collection; sabbatical_report

Italian-American Landscape of the New York-New England Region. - Inguanti, Joseph (2001)
Keywords: dept.art; faculty_collection; sabbatical_report

Pictorial Political Propaganda of the French Court in the Reign of Charles Vii, 1422-1461. - Serchuk, Camille (2001)
Keywords: dept.art; faculty_collection; sabbatical_report

The Human Element Within Societal Structures, Mixed Media Outdoor Sculptural Works. - Sierpinski, Cort (Spring;Art., 2001)
Keywords: dept.art; faculty_collection; sabbatical_report

[Collage and Assemblage Art] - Guagliumi, Arthur (2000)
Keywords: dept.art; faculty_collection; sabbatical_report

Icons, Crosses & Eggs: The Soul and Culture of the Eastern Christian Faith. - Klancko, Robert John; Klancko, Yvonne Shia; Southern Connecticut State University (Southern Connecticut State University, 2009)
Keywords: Art; Europe; Eastern; Exhibitions; Exhibitions; Christian art and symbolism; Exhibitions; Folk art; Orthodox Eastern Church; dept.art; faculty_collection

Light Du Jour (light of the Day) - Phelan, William R. (Createspace, 2009)
Keywords: dept.art; faculty_collection

Easter Eggs & Art: The Robert J. and Yvonne S. Klancko Collection Presented by the Knights of Columbus Museum - Klancko, Robert J.; Klancko, Yvonne S. (Knights of Columbus Museum, 2006)
Keywords: Art collections; Europe; Eastern; Exhibitions; Exhibitions; Christian art and symbolism; Exhibitions; Easter eggs; Exhibitions; Egg decoration; Exhibitions; Folk art; Exhibitions; Klancko; Yvonne S; Klancko; Robert J; dept.art; faculty_collection

100 Creative Drawing Ideas - Audette, Anna Held (Shambhala, 2004)
Keywords: Drawing; Technique; dept.art; faculty_collection

Louis C. Tiffany: The Collected Works of Robert Koch. - Koch, Robert (Schiffer Pub., 2001)
Keywords: Art nouveau; Catalogs; Catalogs; Art glass; Catalogs; Decoration and ornament; Collectors and collecting; History; Glassware; Tiffany; Louis Comfort; 1848-1933; Tiffany Studios (New York; N.Y.); United States; dept.art; faculty_collection

Picturing France in the fifteenth century: The map in BNF MS Fr. 4991 - Serchuk, C. (Imago Mundi, 2006)
A map of France is included in a manuscript, dated to around 1460, entitled A tous nobles, which contains a historical account and genealogy of the French kings. The map was produced in the wake of the Hundred Years War, when conflict with the English challenged both French identity and territory. The map, however, smooths over a century of war to reveal a nation both strong and independent. Through the mapmaker's selection of places, and his use of fluvial boundaries to define the area concerned, he has created an image of France shaped by ideology and history that is wholly in keeping with its location in the manuscript, where the renaming of Gaul as France is described. The map reveals the territory of France to be a critical link between the mythical past and the political present. This connection between history and territory, also reiterated in the text itself, is presented in a graphic format that may be related to contemporary practice of using maps along with legal documents in the resolution of territorial disputes. Seen in the light of the king's claim to the lands ruled by his ancestors, the map thus constitutes a rare medieval example of French national identity expressed in relation to French territory. © 2006 Imago Mundi Ltd.
5 citations (Crossref) [2023-10-31]
Keywords: A tous nobles; Aquitaine; Bibliothèque nationale de France MS Fr. 4991; Burgundy; Catherine de Medici; Charles IV; Charles VII; Edward III; Eurasia; Europe; France; Genealogy; Hundred Years War; Jean Boutillier; Litigation; Manuscript illumination; Map signs; Map structure; Marcomir; National identity; Nicolas de Nicolay; Philip VI; Propaganda; Western Europe; dept.art; historical cartography; ideology; map; map graphics

Invisibility of Blackness: Visual Responses of Kerry James Marshall - Whitehead, J.L. (Art Education, 2009)
1 citations (Crossref) [2023-10-31]
Keywords: dept.art; peer-reviewed

Familiar voices and the need for reform - Connors, K.E. (Real-World Readings in Art Education: Things Your Professor Never Told You, 2000)
Journal Abbreviation: Real-World Read. in Art Educ.: Things Your Prof. Never Told You
Keywords: dept.art

Ceste figure contient tout le royaulme de France. Cartography and national identity in France at the end of the Hundred Years War - Serchuk, Camille (Journal of Medieval History, 2007)
This paper examines a little known map of France made around the middle of the fifteenth century, for a genealogical manuscript of the text known as A tous nobles, conserved today as Bibliothèque nationale de France [BnF] MS fr. 4991. It argues that the map's prominence in the manuscript articulates a notion of French identity based on a bond to the territory of France rather than on fealty to its king. Using other images from the manuscript, it considers the importance of geography to the emergence of French national sentiment at the time of the Hundred Years War. © 2007 Elsevier Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-140-123-972-806 tex.type: [object Object]
Keywords: A tous nobles; Bibliotheque nationale de France MS fr. 4991; Débat des hérauts d'armes de France et d'Angleterre; Evesham Map; Geography; Grandes Chroniques de France; Marcomir; Medieval cartography; National identity; Norman Conquest; Polemical literature; Remanieurs; dept.art